2018
DOI: 10.1093/police/pay028
|View full text |Cite
|
Sign up to set email alerts
|

Deterrence of Online Child Sexual Abuse and Exploitation

Abstract: ‘Cyberspace’ has added a dimension to the ecology of the child and should be a starting point for practitioners (including police) to think about digital media in the context of child sexual abuse. While there is no evidence to suggest that online abuse and exploitation is a more serious offence than crimes occurring offline, the behaviours enabled by social media may present a significant risk factor for some children. This article gives a brief overview of the phenomena and prevalence of online child sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…Other definitional issues arose with broad terms such as culture or poverty , and a suggestion to develop a shared language that does not overemphasise cultural differences. A final definitional and conceptual issue was the distinction of victim vs. perpetrator in light of the challenges from self-generated illegal content [45]. Whilst this analysis clearly argues for a victim-centric approach, there is much complexity underlying how we approach the concept of victimhood and perpetration within TCSA when there are significant mediating factors at play ( “… a lot of these problems on the ground are not exactly preventable” ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other definitional issues arose with broad terms such as culture or poverty , and a suggestion to develop a shared language that does not overemphasise cultural differences. A final definitional and conceptual issue was the distinction of victim vs. perpetrator in light of the challenges from self-generated illegal content [45]. Whilst this analysis clearly argues for a victim-centric approach, there is much complexity underlying how we approach the concept of victimhood and perpetration within TCSA when there are significant mediating factors at play ( “… a lot of these problems on the ground are not exactly preventable” ).…”
Section: Discussionmentioning
confidence: 99%
“…A high proportion of online abuse and exploitation crimes involve children, and their own activities concerning peer-related sexual content has meant that young people are also creating potentially illegal materials [45]. Whilst guidelines published by the National Institute for Health and Care Excellence [46] have differentiated between sexually abusive behaviour and those behaviours that are detrimental to a child’s development, the links between harmful sexual behaviours, pornography, grooming, sexting , and contact sexual offending are poorly understood and conceptualised [45]. The online behaviours of young people, illustrated by large-scale studies such as EU Kids Online , n = 18,709 [47], have highlighted the risk of receiving sexual messages; about one quarter of those receiving such messages self-reported that they had experienced negative emotions resulting from them.…”
Section: Introductionmentioning
confidence: 99%
“…Technological affordances have also been considered in the context of an interaction between design and usage and an example of this is privacy settings, where affordances shape practice in that privacy settings distinguish between public, private or partially private communications. 56 However, as previously noted, users also shape affordances, for example, young people setting up multiple profiles on SNSs to project different selves to different audiences. Earlier work in this area suggested that we can also identify 'social affordances' that refer to interactions between how users respond, the social context and social networks.…”
Section: Technological Affordances and Csammentioning
confidence: 97%
“…But without an evidence base as to their effectiveness their widespread use remains stalled (Prichard et al, 2019). CSEMprevention messages have been recommended because they: (a) are consistent with health prevention models (Quayle & Koukopoulos, 2018); and (b) could be implemented by any agency with the capacity to inject code into HTML pages to trigger actions defined in the page's java script (Prichard et al, 2019). Various agencies have this capacity, including P2P networks, Internet service providers, global search engines, media and communication regulatory bodies (e.g., Australia's Office of the eSafety Commissioner), and law enforcement agencies (Prichard et al, 2019).…”
Section: Warning Messagesmentioning
confidence: 99%